EHD enhanced heat transfer in wavy channel - Kasayapanand N. (2014)
Heat transfer enhancement with electrohydrodynamic (EHD) technique in laminar forced convection inside a wavy channel with different wire electrode arrangements is numerically investigated. The electric field is generated by the wire electrodes charged with DC high voltage. The mathematical modeling includes the interactions among electric field, flow field, and temperature field. The simulation is firstly conducted with the experimental data in case of rectangular flat channel and the results agree very well. Then the modeling is carried out in the case of wavy channel. It is found that the heat transfer coefficient with the presence of electric field increases with the supplied voltage but decreases when the Reynolds number and the distance between the wire electrodes and the wall surface are augmented. The heat transfer enhancement is also dependent on the number of the wire electrodes, the number of wave per length, and the wave aspect ratio. © 2005 Elsevier Ltd. All rights reserved.